A survey about the most representative psychologists and the future of psychology in Arequipa - Arias Gallegos, Walter Lizandro (2019)
This study examines the views of psychology students in Arequipa city, concerning to the most representative psychologists of the town, Peruvian, Latin American, and world wide. Also, it is discussed the views with regard to the future of psychology; in both cases an ad hoc survey was used and applied to 84 psychology students from four universities in Arequipa. It is concluded that students identified the most important psychologists through three consecutive criteria: (1) their academic production, (2) their teaching role, and (3) their presence in the news media. In addition, it was possible to notice that in each university, student’s preferences reflect the mainstream that is cultivated in every study house. With respect to psychology in the future, greater objectivity and scientific rigor, emphasizing technology and neuroscience issues, and areas such as organizational psychology characterize it.